(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
An indirect translation is a translation that is not produced directly from the source text but is instead produced with the help of an intermediary text. As a result of this, there are concerns that the indirect translation will differ from the original source text. Taking this into account, this study attempts to examine the influence of the intermediary text in indirect translation into the Malay language. It involves an indirect translation in Malay entitled Nurani Tanah Melayu, an intermediary text in English entitled The Soul of Malaya and a source text in French entitled Malaisie. More specifically, this study aims to determine whether the use of the English intermediary text in indirect translation into Malay has any effect on the translation in terms of its accuracy to the content of the original source text in French. In order to carry out this study, a comparison is carried out between the source text, the intermediary text and the translation. The findings show that in a number of cases, there are differences between the translation and the original source text, which indeed affects the indirect translation. These differences are in the forms of additions, omissions and alterations. These differences, however, are attributed not only to the use of the intermediary text but also to adjustments made by the translator. Keywords: Indirect translation, Nurani Tanah Melayu, intermediary text, adjustments in translation, effects of translation